The National Committee for Liberation ("ARM"), 1960-1964 : sabotage and the question of the ideological subject - Du Toit, Andries; Du Toit, Andries (Department of Historical Studies, 2017)
Subject Matter: The dissertation gives an account of the history of the National Committee for Liberation (NCL), an anti-apartheid sabotage organisation that existed between 1960 and 1964. The study is aimed both at narrating its growth and development in the context of South Africa in the 1950s and 1960s, and explaining its strategic and political choices. In particular, the reasons for its isolation from the broader muggle against Apartheid and its inability to transcend this isolation are investigated. Sources: Discussion of the context of the NCL's development depended on secondary historical works by scholars such as Tom Lodge, Paul Rich, C.J. Driver and Janet Robertson as well as archival sources. The analysis of liberal discourse in the 1950s and 1960s also drew heavily on primary sources such as the liberal journals Contact, Africa South and The New African. Secondary sources were also used for the discussion of the NCL's strategy in the context of the development of a theory of revolutionary guerrilla warfare after the Second World War: here the work of Robert Taber, John Bowyer Bell, Kenneth Grundy and Edward Feit was central. The history of the NCL itself was reconstructed from trial records, newspapers and personal interviews. Archival sources such as The Karis-Carter collection, the Hoover Institute microfilm collection of South African political documents, the Paton Papers, the Ernie Wentzel papers were also extensively used. Methodology: The discussion of the discourse of liberal NCL members depended on a post-structuralist theory of subjectivity. The conceptual underpinnings of the thesis were provided by on the work of Jacques Lacan, Louis Althusser, Michel Pecheux, Ernesto Laclau, Chantal Mouffe and Slavoj Zizek. Pechcux's elaboration of the Althusserian concept of interpellation formed the basis of a discourse analysis of NCL texts. In the interviews, some use was also made of techniques of ethnographic interviewing developed by qualitative sociologists such as James Spradley. Conclusions: The analysis focused on the way NCL discourse constructed NCL members as "ordinary persons", a subject-position which implied a radical opposition between political struggle and ideological commitment. The NCL's strategic difficulties were related to the contradictions this discourse, related to metropolitan political traditions that valorised civil society, manifested in the context of post-Sharpeville South Africa. These contradictions were explored in terms of the Lacanian notion of the "ideological fantasy". The dissertation thus closes with a consideration, both of the importance of the ideological traditions identified in the analysis of NCL discourse, and the methodological importance of non-reductive conceptualisations of political identity and ideology.